2020
DOI: 10.1080/15298868.2020.1714711
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual humility in the sociopolitical domain

Abstract: A growing body of research has demonstrated the relevance of intellectual humility to a variety of interpersonal and social attitudes and behaviors. There is a need for further replication and expansion of findings about the role of intellectual humility in the sociopolitical domain. We examined sociopolitical intellectual humility (SIH), i.e., a non-threatening awareness of the fallibility of one's views about sociopolitical topics in relation to attitudes toward specific political groups and issues in a U.S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 74 publications
4
36
0
Order By: Relevance
“…This must be interpreted with caution, given the dislike/avoidance of political discussion construct was based on ad hoc items rather than a validated scale. Nevertheless, this finding is consistent with previously observed links between IH and political interest/engagement (Krumrei-Mancuso & Newman, 2020;Porter & Schumann, 2018) and may allay concerns that SIH is reflective of political apathy or diffidence.…”
Section: Discussionsupporting
confidence: 91%
“…This must be interpreted with caution, given the dislike/avoidance of political discussion construct was based on ad hoc items rather than a validated scale. Nevertheless, this finding is consistent with previously observed links between IH and political interest/engagement (Krumrei-Mancuso & Newman, 2020;Porter & Schumann, 2018) and may allay concerns that SIH is reflective of political apathy or diffidence.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with these conjectures, both domain-general and politics-specific IH are associated with less affective polarization and same-party favoritism (Bowes et al, 2020;Krumrei-Mancuso & Newman, 2020), raising the possibility that IH is negatively related to political myside bias. Intellectually humble individuals may be less susceptible to same-party cues when evaluating information given that such individuals may be less affectively connected with same-party cues and more open-minded when faced with politically incongruent information (Nadelhoffer et al, 2020;Stanley et al, 2020).…”
Section: A Step Outside Of the Echo Chamber: Ih And Political Myside Biasmentioning
confidence: 66%
“…IH reflects the propensity to reflect on the accuracy of one's beliefs and seek information impartially (Leary et al, 2017). Preliminary evidence suggests that IH may temper political extremism (Krumrei-Mancuso & Newman, 2020;Porter & Schumann, 2018), insofar as it is linked with open-mindedness and respect for others. Hence, IH may be particularly germane to less political myside bias (Hodge et al, 2020a).…”
mentioning
confidence: 99%
“…10 Recent research have identified significant implications and benefits of applying intellectual humility in various domains, for instance, sociopolitics, religion, education, business and leadership. 7,11,12 Based on the above conceptualization of intellectual humility, we propose that the trait is also beneficial in promoting interdisciplinary collaboration. As discussed below, the core dimensions of intellectual humility may facilitate effective collaborations among members of a health care team.…”
Section: A J P Ementioning
confidence: 99%